Size Matters: Radiocarbon Dates of <200 µg Ancient Collagen Samples with AixMICADAS and Its Gas Ion Source. Issue 2 (7th November 2017) - Fewlass, Helen; Talamo, Sahra; Tuna, Thibaut; Fagault, Yoann; Kromer, Bernd; Hoffmann, Helene; Pangrazzi, Caterina; Hublin, Jean-Jacques; Bard, Edouard
Abstract: For many of archaeology's rarest and most enigmatic bone artifacts (e.g. human remains, bone ornaments, worked bone), the destruction of the 500 mg material necessary for direct accelerator mass spectrometry (AMS) dating on graphite targets would cause irreparable damage; therefore many have not been directly dated. The recently improved gas ion source of the MICADAS (MIni CArbon DAting System) offers a solution to this problem by measuring gaseous samples of 5–100 µg carbon at a level of precision not previously achieved with an AMS gas ion source. We present the results of the first comparison between "routine" graphite dates of ca. 1000 µg C (2–3 mg bone collagen) and dates from aliquots of gaseous samples of <100 µg C (<0.2 mg bone collagen), undertaken with the highest possible precision in mind. The experiment demonstrates the performance of the AixMICADAS in achieving reliable radiocarbon measurements from <0.2 mg collagen samples back to 40, 000 14 C BP. The technique has great implications for resolving chronological questions for key archaeological artifacts.